Pengaruh Konotasi Negatif Akronim Aplikasi Pemerintah dan Implikasinya terhadap Persepsi Publik: Studi Kasus 11 Aplikasi Pemerintah Indonesia - Lailatul Aqromi, Nur; Khodijah, Siti; Hayuningtyas, Nina (Kajian Linguistik dan Sastra, 2024)
This study aims to investigate the impact of negative connotations in acronyms used by 11 Indonesian government applications. The research focuses on understanding public perception of these acronyms, especially those with vulgar and sexist connotations. The methodology includes a combination of observation and survey methods. Primary data were collected by recording acronyms from official government websites, while secondary data were obtained through a questionnaire survey with 60 respondents (38 females and 22 males). The results show that 52.4% of respondents are aware of these acronyms, and over 90% perceive them as vulgar. Moreover, more than half of the respondents find these acronyms inappropriate for public services, with 52.4% associating them with gender-specific sexual connotations. The study highlights the need for a more culturally sensitive approach in branding public services to avoid alienating the public.